Youtube as a Teaching Media to Enggage Students’ Interest iIn Learning Speaking of English Language Learners At Universitas Muhammadiyah Kotabumi - Sartipa, Dewi; Munisah, Eny; Sri Kuning, Dewi (e-Journal of Linguistics; Vol 16 No 2 (2022): ejl-JulyDO - 10.24843/e-jl.2022.v16.i02.p09, 2022)
The popular social media network today is Youtube. In the context of teaching and learning, Youtube can be used as a learning medium. Youtube can increase students' interest in learning Speaking. The benefit of the results of this study is to describe how students are interestedtouse  Youtube in a learning medium for Speaking. This research uses descriptive quantitative research methods. The instrument of this research is a questionnaire. The results in this research is the use of Youtube as a learning medium played a significant positive role in increasing students' interest in learning. Youtube also has a  positive role to increase students' interest in learning.